IMPROVEMENT OF PROFESSIONAL COMPETENCE OF ARABIC LANGUAGE TEACHERS GRADE 1 THROUGH TA'HIL TEACHERS TARBIYATUL MU'ALLIMAT AL-ISLAMIYAH PONDOK PESANTREN WALI SONGO NGABAR - Ismi Mazza; Dzulfiqor Abdurrohman; M. Zainal Arif; Rido Kurnianto (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This study aims to evaluate the effectiveness of the ta'hil program in improving the professional competence of Grade 1 Arabic language teachers at Wali Songo Ngabar Islamic Boarding School and to analyze efforts to enhance the professional competence of Grade 1 Arabic language teachers through ta'hil for Tarbiyatul Mu'allimath Al-Islamiyah teachers. Using field research methods and a descriptive qualitative approach, this study directly observes efforts to improve teacher competence through ta' hil Tarbiyatul Mu'allimat Al-Islamiyah. The research focus includes guidance on preparation, implementation, and evaluation of learning. The results show that the ta'hil program contributes significantly to improving teachers' abilities in mastering four language skills (maharah) and learning evaluation techniques. Grade 1 Arabic language teachers who participated in this program demonstrated improvements in material readiness, classroom management, and the ability to deliver lessons effectively. Positive impacts were observed not only in teacher performance but also in students ability to absorb the material. This study concludes that the ta'hil program is an effective means for Wali Songo Ngabar Islamic Boarding School to develop the professional competence of Arabic language teachers.